Occasionally stigmatized: how the frequency and context of use influence perceptions of intermittent smokers. (4th May 2019) - Berg, Michael B.; Lin, Linda
Abstract: Background: There is an established stigma against smoking in which smokers are less socially accepted and perceived as having more character flaws than nonsmokers. Yet all of the studies of antismoking stigma have solely focused on daily, habitual use. Intermittent smokers, individuals that smoke less than one cigarette per day and often only a few each month, are becoming a larger proportion of smokers in the U.S. and worldwide. Method: The current research consisted of two online experimental surveys that tested perceptions of intermittent smokers. Study 1 compared impressions of individuals with three different frequencies of smoking (a nonsmoker, an occasional smoker, and a daily smoker) while Study 2 compared three different contexts of use (a nonsmoker, a social smoker, and a habitual smoker). Results: The combined results of these two studies found that there was a moderate stigma against intermittent users where they were seen more negatively than nonsmokers and more positively than daily smokers when rated by nonsmoking participants. In particular, of those who smoked intermittently, female targets and, in limited circumstances, those who had a smoking-related illness were more stigmatized and rated as having less desirable character traits than comparable nonsmokers. Participants who were ex-smokers or current smokers, however, did not perceive intermittent smokers more negatively than nonsmokers. Conclusions: Taken together, these findings revealed that intermittent smokers may be moderately stigmatized in certain situations and contexts, but that the nature of these social assessments varies heavily by gender, health status, and the smoking history of the perceiver.